SELF-REGULATED LEARNING AND DIGITAL LEARNING ENVIRONMENT: ITS’ EFFECT ON ACADEMIC ACHIEVEMENT DURING THE PANDEMIC - Nani Sutarni; M Arief Ramdhany; Achmad Hufad; Eri Kurniawan (Jurnal Cakrawala Pendidikan, 2021)
The unprecedented changes in the education sector due to the recent pandemic demand teachers and students to adapt to new ways of learning via online platforms. A plethora of latest research has investigated various topics such as online learning platforms, online learning materials, and teacher/student perceptions; however, little is known about the link between online learning and achievement. Occupying this lacuna, this study specifically sought to examine the relationship between self-regulated learning (SRL), the digital learning environment, and student’ academic achievement during the pandemic.  The population of this research was 1,800 students (freshmen, sophomore, junior, and senior class) enrolled for the Introduction to Management course at a state university in Bandung, Indonesia. Selected using a proportionate random sampling, 317 students participated as the respondents.  The data were collected through questionnaire surveys, while the Structural Equation Model (SEM) was employed to analyze the interrelationship among the construct variables.  The results of this study show that promoting SRL may affect the optimization of the digital learning environment and academic achievements.  Students with better self-regulated learning ability can somehow optimize their digital learning environment and be more progressive in terms of academic achievement.